Recognition of Sins, the Way of Forgiveness and Purification Through Jesus Christ Based on 1 John 1: 9 - Juita Sinambela; Janes Sinaga; Beni Chandra Purba (International Journal of Scientific Multidisciplinary Research, 2023)
Crime is everywhere, from drugs, murder, drugs, free sex, to domestic violence which ends in divorce. This event is often encountered because of sin, where after the fall humans tend to commit sins. To overcome this problem, a savior is needed, namely Jesus Christ, where everyone needs to realize their mistakes by asking for forgiveness and repenting. The purpose of this research is for everyone to be aware of the problem of sin, and realize the need for salvation so that the problem of sin can be overcome which is increasingly rampant in every aspect of life. This study uses a descriptive qualitative method by analyzing data from reliable sources and concluding it according to the research object. Sin can only be resolved by Jesus Christ through his sacrifice on the cross. Everyone who wants to be saved just needs to come to Jesus to admit his mistake and believe in him as a savior